PERMASALAHAN INDUSTRI KECIL PASCAGEMPA BUMI: SURVEI PADA BEBERAPA INDUSTRI DI KABUPATEN KLATEN, JAWA TENGAH - Krisnadewara, P. Didit; Susilo, Y. Sri (KINERJA, 2006)
The purpose of this research is to recognize and analyze the problems that small industries face due to the earthquake disaster in Klaten Region, Central Java. The problems include damages, entrepreneurs/craftsmen’s anxieties, and entrepreneurs/craftsmen’s’ urgent needs. Data is compiled by field survey and in-depth interview. Small industries that were surveyed were readymade wear industry, earthenware vessels and ceramics industry, furniture industry, woven cloth industry, and roof-tiles industry. Datas are analyzed with descriptive analysis method. The resultof the survey is that damages occurred especially on buildings, production tools/equipments, and market potency. The entrepreneurs/craftsmen’s anxieties are the loss/decrease of customers, the disturbance of production and distribution process, lack of ability to afford the financial obligations, and have to lay off the employees. And third; the urgent needs are building repair, tool/equipment repair, and additional business capital. Finally, this research talks about time of business recovery estimation.Keywords: business problems, small industry, post-earthquake, Klaten Region